Direct photonic etching of electrical materials. (17th July 2007) - Jackson, Mark J.; Robinson, Grant M.
Multiwavelength Diode Pumped Solid State (DPSS) lasers allows operations such as micromachining in a variety of materials such as ceramics, metals and polymers. A series of experiments was performed to investigate how the protective gas environment and gas pressure affect the ability to cut and machine silicon steel. Results from this study reveal that traditional plasma-controlling gases have a detrimental effect on the surface morphology of machined electrical components. This paper discusses the theory behind direct photonic etching and explains how the machining of thin plates of silicon steel can benefit the rapid production of electrical components such as transformer cores and dynamo pole pieces.